Creatures of passage - Yejide, Morowa (Akashic Books, 2021)
"Nephthys Kinwell is a taxi driver of sorts in Washington, DC, ferrying passengers in a 1967 Plymouth Belvedere with a ghost in the trunk. Endless rides and alcohol help her manage her grief over the death of her twin brother, Osiris, who was murdered and dumped in the Anacostia River. Unknown to Nephthys when the novel opens in 1977, her estranged great-nephew, ten-year-old Dash, is finding himself drawn to the banks of that very same river. It is there that Dash--reeling from having witnessed an act of molestation at his school, but still questioning what and who he saw--has charmed conversations with a mysterious figure he calls the "River Man." When Dash arrives unexpectedly at Nephthys's door bearing a cryptic note about his unusual conversations with the River Man, Nephthys must face what frightens her most. Morowa Yejidé's deeply captivating novel shows us an unseen Washington filled with otherworldly landscapes, flawed super-humans, and reluctant ghosts, and brings together a community intent on saving one young boy in order to reclaim itself."--Amazon.